COMPARATIVE STUDY OF THE INFLUENCE OF CONVENTIONAL FINANCING AND GREEN FINANCING ON CORPORATE CAPITAL STRUCTURE IN ACEH PROVINCE - Muttaqien; Wardhiah; Rico Nur Ilham; Alya Maulisa; Muti Miftahul Jannah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze and compare the impact of Conventional Financing and Green Financing on corporate capital structure, measured by the Debt to Equity Ratio (DER), for firms in Aceh Province. Employing a quantitative comparative method on corporate financial statement data spanning the 2021-2024 period, the research found that the limited access to green financing and the smaller scale of green-funded projects in Aceh suggest constraints in the green market. Nevertheless, a comparative analysis reveals a significant difference between the influence of conventional financing and green financing on the capital structure in Aceh Province. Empirically, Green Financing positively impacts the strengthening of the firm's capital structure, positioning it as a strategic alternative toward sustainable economic development in Aceh. This conclusion underscores the critical role of Green Financing as a unique strategic financial determinant, providing practical implications for corporate management in Aceh to integrate sustainability aspects into funding decisions to achieve long-term capital structure optimization.